2014
DOI: 10.1097/ijg.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1-associated Candidate Epithelial Pathomechanisms in Exfoliation Glaucoma

Abstract: Results of the present study support ocular epithelia-specific LOXL1 functions in exfoliation glaucoma that may include both dysregulated extracellular matrix cross-linking activity and cellular mechanisms involving a role for LOXL1, in direct interaction with Snail1, in promoting epithelial to mesenchymal transition (EMT) and a potential shift towards fibrogenic epithelial cell phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…This is similar to other epigenetic regulators that have both enzymatic activity dependent and independent functions. For example, JMJD3, a well-known histone lysine demethylase has demethylase independent functions as well 40,41 , and the lysyl-oxidases LOXL1 and LOXL2 have enzymatic activity-independent functions in EMT 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to other epigenetic regulators that have both enzymatic activity dependent and independent functions. For example, JMJD3, a well-known histone lysine demethylase has demethylase independent functions as well 40,41 , and the lysyl-oxidases LOXL1 and LOXL2 have enzymatic activity-independent functions in EMT 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inflammation has also been suggested in migratory failure and subsequent deposition of aberrant proteinaceous materials in affected tissues in conjunction with other molecular actors. 71,[103][104][105][106][107][108] Finally, our comorbidity analysis in the BioVU EHR indicated XFS association with several chronic inflammatory dermatological, musculo-skeletal, respiratory and infectious conditions. Moreover, extracellular matrix dysregulation is also suggested by our PheWAS results indicating XFS comorbidity with Vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Guo et al recently identified the LOX mutation that causes familial TAAD: the Ser280Arg mutation produced a less active variant that led to disorganised elastic fibres and increased collagen in patients’ aortas [127]. Several reports have described an association between LOXL1 and glaucoma, specifically in the early stages of the elastic fibre disorder exfoliation syndrome (XFS) [76,[128], [129], [130], [131]]. LOXL1 colocalised with elastin, fibrillin-1 and fibulin-4, which were also upregulated, and its expression was enhanced by TGFβ1 and other XFS-associated stimuli in Tenon’s capsule fibroblasts [76].…”
Section: Functional Modifiers Of Elastic Fibresmentioning
confidence: 99%